Marketing of Tourism Services - A Case Study on AP Tourism (APTDC Ltd) Visakhapatnam - Sheaba Rani, M. (Indian Journal of Marketing, 2007)
Andhra Pradesh Tourism Development Corporation is extending its services so as to cater to the needs of different groups of clientele with the concept of tourism development and has been giving emphasis not only to increase the revenue for the Government but also to satisfy the growing needs of different groups of clientele. The company was incorporated in February 1976 as a subsidiary of Andhra Pradesh State Road Corporation (APSRTC) in the name of Travel And Tourism Development Corporation Private Ltd with an authorized and paid up capital of 100 and 13 lakhs respectively. The company was registered in March 1980 under the name Andhra Pradesh Travel and Tourism Development Corporation Ltd. The main objective of the company is to develop Tourism in the state. The main aim is to position the state as the "Dream - Destination" of the Country.